CCN1 Enhances Tumor Immunosuppression through Collagen‐Mediated Chemokine Secretion in Pancreatic Cancer - Hongjie Fan; Huzi Zhao; Lili Gao; Yucheng Dong; Pei Zhang; Pengfei Yu; Yunfei Ji; Zhe‐Sheng Chen; Xinmiao Liang; Yang Chen (Advanced Science)
Abstract Pancreatic ductal adenocarcinoma (PDAC) is characterized by a dense, immunosuppressive tumor microenvironment (TME) that limits therapeutic efficacy. This study investigates the role of cellular communication network factor 1 (CCN1, also known as Cyr61), an extracellular matrix‐associated protein, in modulating the TME of PDAC. It is demonstrated that Ccn1 promotes PDAC progression by upregulating collagen and chemokine expression, thereby facilitating immune cell exclusion and enhancing tumor growth. Using a Ccn1‐deficient PDAC model, decreased collagen and chemokine levels are observed, resulting in increased infiltration of cytotoxic immune cells and reduced myeloid‐derived suppressor cells (MDSCs). Furthermore, Ccn1‐deficient tumors exhibit heightened sensitivity to gemcitabine and show enhanced responsiveness to anti‐programmed cell death 1 (anti‐PD1) therapy. Mechanistically, Ccn1 regulates chemokine production through collagen expression, with chemokine levels remaining suppressed even upon interferon‐gamma treatment in collagen‐deficient cells. These findings highlight Ccn1 as a potential therapeutic target that reprograms the TME to enhance the efficacy of both chemotherapy and immunotherapy in PDAC, providing a novel approach for overcoming immune resistance in PDAC.